The Impact of Problem-Based Learning (PBL) on Student Achievement in Engineering Subject Material at Vocational College Kuantan, Pahang - Amiruddin, Mohd Hasril; Sumarwati, Sri; Amat, Kusnin (Online Journal for TVET Practitioners, 2021)
Problem-Based Learning (PBL) is a student-centered teaching approach. This study was conducted to identify the impact of Problem-Based Learning (PBL) on student achievement in engineering subject material at Vocational College Kuantan, Pahang. The study design used in this study was a quasi-experimental type involving two study groups namely the experimental group and control group. The experimental group in this study was referred to as the group exposed to the PBL teaching method. Whereas the control group is a group that uses traditional teaching strategies that use the standard (lecture) method commonly practiced, however, the content of teaching for the subject of engineering materials is the same as the experimental group. The respondents in this study were 30 students of 1st-semester Fabrication Welding Metal that selected using purposive sampling. To determine the level of student achievement, the researcher presents an achievement test for the subject of engineering materials. The results of this study were analyzed by independent t-test using Statistical Package for The Social Science (SPSS) version 21.0. This study found that student achievement in the experimental group was higher than the control group achievement. This shows that the PBL teaching method affects students' achievement in the subject of engineering materials at Vocational College Kuantan, Pahang. It is hoped that the findings of this study can serve as a reference to various stakeholders in designing and implementing problem-based learning methods to produce skilled thinkers who are critical in their work, problem-solving skills, and lifelong learning.